Cognitive behaviour therapy (CBT) as a psychological intervention in the treatment of ARFID for children and young people. (22nd February 2023) - Howard, Maxine; Hembry, Pippa; Rhind, Charlotte; Siddall, Amy; Uddin, Mohammed Fahim; Bryant-Waugh, Rachel
Abstract: Avoidant Restrictive Food Intake Disorder (ARFID) is a condition characterised by a disturbance in eating behaviour that leads to a significant negative impact on physical, social and nutritional health. The diagnosis of ARFID relies on a comprehensive, multi-disciplinary assessment to understand the individual's history, physical, social and mental health risk, and any co-occurring mental health difficulties. Consensus guidance suggests that psychological treatment, alongside medical and dietetic input is delivered with consideration of any appropriate adaptions to accommodate developmental stage and/or common co-occurring presentations. This paper has been authored by clinicians working in an out-patient setting for children and adolescents with ARFID, and focuses on the presentation and assessment of ARFID and cognitive behavioural therapy (CBT) approaches that can help children, young people and their families. After an introductory section, the paper is split into four sections: assessment of ARFID; drivers of avoidant restrictive eating behaviour; multi-disciplinary formulation and intervention planning; and treatment. The treatment section provides an overview of the available research on CBT for ARFID, and a brief summary of the broader evidence base for CBT in children and young people with anxiety. Following a review of the evidence base, three case descriptions are provided to illustrate the clinical application of CBT where fear-based avoidance is the main driver. The paper concludes with practice points for clinicians to take forward when working with children and young people with ARFID. Key learning aims: (1) To be aware of the international consensus for the use of psychological interventions as a component of ARFID treatment alongside medical and dietetic input. (2) To understand that ARFID is characterised as a disturbance of eating behaviour, and as such, psychological intervention should target the drivers of this disturbance to promote behavioural change. (3) To gain an overview of the multi-disciplinary team assessment as an important tool to understand the contribution of each of the three drivers proposed to underpin an ARFID presentation. (4) To recognise when a CBT approach might be indicated, the current best evidence base for CBT for ARFID and how to adapt CBT to accommodate developmental stage and/or common co-occurring presentations.